Rye (Secale cereale L.) arabinoxylans: molecular structure, physicochemicals properties and the resulting pro-health effects - Dynkowska, Wioletta (Plant Breeding and Seed Science, 2020)
Arabinoxylans are an essential component of dietary fiber, and their health-promoting properties are determined mainly by the content and structural features their biopolymers. Rye bread is particularly rich in these compounds; their unique features in the context of content and chemical structure of rye arabinoxylans make it a valuable component od daily diet. Long-term studies have shown the positive effect of these compounds in the aspect of prevention of civilization diseases such as type 2 diabetes, obesity, and cardiovascular diseases. Among the description of the physicochemical properties and diversity of arabinoxylans, the article contains a collection of the most important reports regarding the health-promoting effects of these polymers, as well as their metabolism in the human body.